2022
DOI: 10.3390/cancers14020388
|View full text |Cite
|
Sign up to set email alerts
|

Distal Gastrectomy for Symptomatic Stage IV Gastric Cancer Contributes to Prognosis with Acceptable Safety Compared to Gastrojejunostomy

Abstract: Background: The prognostic prolongation effect of reduction surgery for asymptomatic stage IV gastric cancer (GC) is unfavorable; however, its prognostic effect for symptomatic stage IV GC remains unclear. We aimed to compare the prognosis of gastrectomy and gastrojejunostomy for symptomatic stage IV GC. Methods: This multicenter retrospective study analyzed record-based data of patients undergoing palliative surgery for symptomatic stage IV GC in the middle or lower-third regions between January 2015 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Tumor stage was classi ed according to the seventh edition of the International Union against Cancer tumor-nodemetastasis staging system for gastric cancer, while lymph node stations were numbered according to the de nitions of the Japanese Gastric Cancer Association [14]. Operative complications were classi ed according to the Clavien-Dindo classi cation [15]. This study was approved by the Institutional Review Board of Hiroshima University (No.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor stage was classi ed according to the seventh edition of the International Union against Cancer tumor-nodemetastasis staging system for gastric cancer, while lymph node stations were numbered according to the de nitions of the Japanese Gastric Cancer Association [14]. Operative complications were classi ed according to the Clavien-Dindo classi cation [15]. This study was approved by the Institutional Review Board of Hiroshima University (No.…”
Section: Methodsmentioning
confidence: 99%
“…First, reduction of immunosuppressive tumor burden may have extended the prognosis, potentially minimizing the chance that the tumor will lead to disease progression and further metastases. Second, it is suggested that chemotherapy compliance may be improved by PTR in symptomatic patients ( 13 , 24 ). The actual mechanism of how PTR may contribute to improved outcomes remains not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in postoperative complications between the groups of distal gastrectomy and gastrojejunostomy. It can be said that distal gastrectomy can be safely performed even in patients with stage IV gastric cancer ( 24 ). In situations where surgical resection would not be expected to cause significant complications, the approach of PTR as needed seems reasonable for patients with stage IV GNEC.…”
Section: Discussionmentioning
confidence: 99%
“…GC is the fifth most common cancer diagnosed worldwide and the third leading cause of death by cancer. The overall survival has improved due to early cancer detection and improved standard-of-care cancer therapies, including tailored treatment based on tumour molecular biology [19,20].…”
Section: Gastric Cancermentioning
confidence: 99%